2020
DOI: 10.1108/ijcthr-01-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Do expectations towards Thai hospitality differ? The views of English vs Chinese speaking travelers

Abstract: Purpose This paper aims to shed light on differences in the patterns of online rating behavior that Chinese- and English-speaking travelers adopt when making hotel reviews on TripAdvisor. Design/methodology/approach A dual analysis was conducted on 800 online reviews for eight hotel brands. The brands, which are currently operating in Bangkok City, are considered to be representative of their categories. The hotels were selected based on their abilities to meet the quantitative and qualitative requirements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…The attribute "room" was presented in most of the studies analyzed during article reviews, as shown in Table 1. Many of these studies identified this attribute as a positive comment generator (Alrawadieh & Law, 2019;Lee et al, 2020;Sann & Lai, 2020a), and linked it to customer satisfaction (Herjanto et al, 2017;Liu et al, 2017;Padma & Ahn, 2020;Wu et al, 2017). On the other hand, there were also studies that corroborated the results of this research, by observing the attribute "room" as a negative comment generator (Hu et al, 2019;Köseoglu et al, 2019).…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…The attribute "room" was presented in most of the studies analyzed during article reviews, as shown in Table 1. Many of these studies identified this attribute as a positive comment generator (Alrawadieh & Law, 2019;Lee et al, 2020;Sann & Lai, 2020a), and linked it to customer satisfaction (Herjanto et al, 2017;Liu et al, 2017;Padma & Ahn, 2020;Wu et al, 2017). On the other hand, there were also studies that corroborated the results of this research, by observing the attribute "room" as a negative comment generator (Hu et al, 2019;Köseoglu et al, 2019).…”
Section: Discussionsupporting
confidence: 58%
“…Research that used UGC of hotels in China revealed that Chinese guests expect personalized service, while North American guests prefer standardized service (Ying et al, 2020); the behavior of guests of different nationalities toward quality attributes of hotels in the United Kingdom is influenced by cultural context (Sann & Lai, 2020b); in hotels in the United Kingdom, Asian guests encounter more service failures with respect to the engineering aspect of operations (room equipment issues), while non-Asian guests encountered more service failures in housekeeping (toilets, public areas, cleaning, and bedding) (Sann & Lai, 2020a).…”
Section: Hotel Service Qualitymentioning
confidence: 99%
See 3 more Smart Citations